Hubungan Pelaksanaan Patient Centered Care (PCC) dengan Kepuasan Pasien Rawat Inap - Melda Yulia (Syntax Corporation Indonesia, 2023)
Patient centered care (PCC) is a health service activity that is collaborative between health workers, patients and families in supporting the treatment needs of patients in hospitals. The goal is health workers from the patients themselves and their families to the services that have been carried out by health in the hospital. This study aims to determine the relationship between the implementation of patient centered care with inpatient satisfaction at Mitra Sejati General Hospital. The type of research is quantitative with a cross-sectional design which was conducted in July 2022 at Mitra Sejati General Hospital with purposive sampling technique. The total population in this study were all inpatients at the RSU. True Partners during the month of June. with a total sample of 110 hospitalized patients. The instrument in this study used a questionnaire. The data obtained in this study were analyzed by Spearmen Rank correlation analysis. The results showed that there was a relationship between patient centered care and satisfaction of inpatients at Mitra Sejati Hospital with a p value of 0.001 (p<0.05) and an r value of 0.656 which was included in the 0.600-0.799 interval and was classified as a strong category. It can be said that it is okay to implement patient centered care to increase the level of satisfaction of inpatients at Mitra Sejati Hospital. Therefore, it is recommended that the hospital conduct socialization in the form of education on the implementation of patient centered care on a regular basis to all health in the hospital. The creation of patient satisfaction will determine the good image and accreditation assessment of Mitra Sejati Hospital in the future.